Delayed school start times and adolescent sleep: A systematic review of the experimental evidence. (August 2016) - Minges, Karl E.; Redeker, Nancy S.
Summary: Many schools have instituted later morning start times to improve sleep, academic, and other outcomes in response to the mismatch between youth circadian rhythms and early morning start times. However, there has been no systematic synthesis of the evidence on the effects of this practice. To examine the impact of delayed school start time on students' sleep, health, and academic outcomes, electronic databases were systematically searched and data were extracted using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Six studies satisfied selection criteria and used pre-post, no control (n = 3), randomized controlled trial (n = 2), and quasi-experimental (n = 1) designs. School start times were delayed 25–60 min, and correspondingly, total sleep time increased from 25 to 77 min per weeknight. Some studies revealed reduced daytime sleepiness, depression, caffeine use, tardiness to class, and trouble staying awake. Overall, the evidence supports recent non-experimental study findings and calls for policy that advocates for delayed school start time to improve sleep. This presents a potential long-term solution to chronic sleep restriction during adolescence. However, there is a need for rigorous randomized study designs and reporting of consistent outcomes, including objective sleep measures and consistent measures of health and academic performance.